Diagnostic Significance of Serum Long Noncoding HOX Antisense Intergenic Ribonucleic Acid in Patients with Hepatitis B Virus Related Hepatocellular Carcinoma - Pan, Yue; Cai, Meng; Zhang, Fan; Liu, Xiaoming; Li, Menghua; Xie, Bingxin; Li, Ju (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors and the third leading cause of cancer-related mortality. Extensive literature suggests that long noncoding RNAs play a role in the progression of HCC and hold potential as diagnostic biomarkers for this disease. Materials and Methods: We examined the serum levels of HOX antisense intergenic RNA (HOTAIR) in 49 hepatitis patients, 31 liver cirrhosis (LC), and 37 HCC patients using quantitative real-time polymerase chain reaction. Correlations between serum HOTAIR levels and clinical data were evaluated in HCC patients. The receiver operating characteristic curve was utilized to analyze the diagnostic potency of HOTAIR. Results: The HOTAIR levels in serum were significantly higher in HCC patients compared to those with hepatitis (P = .003) and LC patients (P = .048). There was a significant association between the serum levels of HOTAIR and positivity of hepatitis B e antigen (HBeAg) (P = .039) as well as portal vein tumor thrombus (P = .040) in HCC patients. The area under the curve (AUC) for HOTAIR for distinguishing HCC from hepatitis and LC was 0.697. The combined AUC for HOTAIR, HBeAg, and alpha-fetoprotein (AFP) was 0.777. Conclusion: Serum HOTAIR functions as a potential diagnostic marker for hepatitis B virus-related HCC. Combining HOTAIR with clinical data and AFP can reinforce the diagnostic precision on HCC. Cite this article as: Pan Y, Cai M, Zhang F, et al. Diagnostic significance of serum long noncoding HOX antisense intergenic ribonucleic acid in patients with hepatitis B virus related hepatocellular carcinoma. Turk J Gastroenterol. 2024;35(5):391-397